Vibration–rotation interaction potential for H2O–A system. (April 2015) - Starikov, V.I.
Abstract: The contact transformation method is used to derive an effective interaction potential for H2 O–A system. The expressions for the second order vibrational and rotational correction terms are obtained. The contributions of the third order, which take into account the Coriolis and Fermi resonances in H2 O molecule, are obtained too. The matrix elements of a transformed interaction potential that are necessary for calculating the broadening parameters of H2 O lines perturbed by mono-atomic gases are presented. Highlights: The effective interaction potential for H2 O–atom system was obtained. It depends on the rotational operators and vibrational quantum numbers of H2 O molecule. The potential determines the vibrational and rotational dependence of the interruption functions.